Factor VII activating protease (FSAP) in thrombosis and haemostasis in vivo - Subramaniam, Saravanan; Justus Liebig University Giessen (My University, 2014)
Factor VII activating protease (FSAP), a serine protease produced in the liver (plasma conc.12 microgramm/mL) has been associated with cardiovascular diseases. In vitro studies revealed that FSAP has a dual function in the coagulation system via inhibition of tissue factor pathway inhibitor (TFPI) and activation of pro-urokinase (pro-uPA). Even though functional polymorphism in the FSAP gene is linked with cardiovascular diseases, due to contradictory clinical observations as well as its dual role in the coagulation system in vitro, the real function and mechanistic aspects of FSAP is ambiguous. To identify the actual function of FSAP in thrombosis and haemostasis, we characterized the FSAP deficient mice using various in vivo and ex-vivo mouse models. Our results showed that in pulmonary thromboembolism model FSAP-/- mice had a significantly higher survival than WT littermates (p smaller than 0.01). The carotid artery injury as well as mesenteric arteriole models revealed that the occlusion time was significantly increased in FSAP-/- mice (p smaller than 0.01). Partial venous thrombosis (PVT) showed a trend in the reduction of total thrombus content and thrombus weight in FSAP-/- mice. Western blotting analysis of plasma samples as well as immunohistochemical analysis of thrombotic carotid arteries and lung tissue extracts showed a slightly increased TFPI expression in FSAP-/- mice when compared to the WT littermates. In situ and gel-based casein zymography showed that FSAP-/- mice had more uPA than the WT littermates. Plasma samples from all these models did not show any influence of plasminogen levels. In vitro analysis of FSAP on platelet TFPI demonstrated that FSAP could inhibit not only the circulating beta form of TFPI but also the platelet derived alpha form of TFPI. Tail-bleeding assay revealed that more than 80% of FSAP-/-mice showed re-bleeding incidences compared to WT littermate controls. The clinical relevance of Marburg-I polymorphism is not well understood because of contradictory observations in various studies. Interestingly, our mice models revealed that the endogenous FSAP plays a key role in extrinsic coagulation cascade via inhibition of TFPI.

Die Faktor VII aktivierende Protease (FSAP), eine in der Leber synthetisierte Serinprotease (Plasmakonzentration: 12 µg/ mL), spielt eine Rolle bei kardiovaskulären Erkrankungen. In vitro Studien zeigten, dass FSAP eine duale Rolle in der Hämostase innehat. Einerseits wirkt FSAP prokuagolatorisch durch Hemmung des Gewebsfaktor-Plasminogen Inhibitors(TFPI), andererseits fibrinolytisch durch Aktivierung der Prouro- kinase (pro-uPA). Obwohl der funktionale Polymorphismus des FSAP-Gens mit kardiovaskulären Erkrankungen verbunden ist, bleibt die Funktion und Wirkungsweise von FSAP aufgrund widersprüchlicher klinischer Untersuchungen wie auch seiner dualen Rolle im Hämostasesystem, unklar. Zur Aufklärung der Funktion von FSAP in Hinsicht auf Thrombose und Hämostase wurden FSAP-defiziente Mäuse in verschiedenen in vivo und ex vivo Modellen getestet. Unsere Ergebnisse zeigten, dass FSAP-/- Mäuse in einem Lungen-Thrombose-Embolie-Modell eine signifikant höhere Überlebensrate aufwiesen als WT-Mäuse (p < 0.01). Bei Verletzung der Karotis-Arterie oder der Mesenterial-arteriole war die Okklusionszeit bei FSAP-/- Mäusen signifikant erhöht (p < 0.01). Eine partiale Venenthrombose (PVT) zeigte tendenziell eine Verringerung des Thrombus in Größe und Gewicht. Westernblot-Analysen von Plasmaproben wie auch immunohistochemische Untersuchungen an thrombotischen Karotis-Arterien und Lungenextrakten ergaben einen leichten Anstieg der TFPI-Expression bei FSAP-/- Mäusen verglichen mit WT-Mäusen. In der In-situ-Zymographie sowie Gel basierenden Kasein-Zymographie zeigten FSAP-/- Mäuse gegnüber WT-Mäusen höhere uPA-Spiegel. Plasmaproben aus allen Modellen zeigten keinen Einfluss von FSAP auf die Plasminogenkonzentration. In vitro Untersuchungen an Plättchen-TFPI zeigten, dass FSAP nicht nur die zirkulierende ß-Form von TFPI, sondern auch die platelet-derived alpha-Form von TFPI hemmt. Bei Messungen der Blutungszeit durch Verletzung des Schwanzes der Mäuse neigten mehr als 80% der FSAP-/- Mäuse zu wiederholtem Bluten gegenüber WT-Mäusen. Die klinische Relevanz des Maburg I Polymorphismus ist aufgrund der widersprüchlichen Beobachtungen an Venenthrombose-Modellen wenig verstanden. Unsere Mausmodelle zeigten, dass endogenes FSAP eine Schlüsselrolle bei der extrinsischen Blutgerinnungskaskade durch Hemmung von TFPI innehat.
Faktor VII aktivierende Protease (FSAP) in Thrombose und Hämostase in vivo
Keywords: ddc:610